Survey of honey production method in Jimma Horro District, Kellem Wollega Zone Oromia Ethiopia - Soresa Shuma Abdisa; Abdisa Abraham Challa; Tolera Kuma (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The study was conducted in Jimma Horro Weredas of Kellem Wollega Zone of Ethiopia to assess beekeeping production classifications. Three kebeles peasant associations (Tibe, Kaba Sayo and Gille) were purposively selected of which 144 respondents; 48 from each agro-ecology were used for data collection. Around 90% of respondents got bee collections by holding groups while 2 and 8% get their cluster by purchasing and since parentages as ability separately. The mean honeybee cluster holding of the illustration defendants for old-style, intermediate and modern hives were 5.47, 3 and 1.3 Semi organized form was established to accumulate major statistics. The organized records were deliberate by evocative figures and the results were restrained through tables and charts. The mainstream (90%) of the defendants found beekeeping by holding groups. Honey was calm double a year beginning May to June and November to January. The defendants designated that, they have attention to improve beekeeping smears in the part. So the management and (NGOs) would funding by exercise them on how to achieve honey bee flora, and giving frame honey bee tools to improve the honey yield is similarly exact significant to boost the yields of beekeeping in the assessment part.